2022
DOI: 10.1016/j.rbms.2021.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Is perceived inability to procreate associated with life satisfaction? Evidence from a German panel study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Nonetheless—as noted above—there are good reasons to study self-perceived infertility. Self-perception measures are often the only measures available to us in surveys, and self-perceived infertility has been associated with both infertility-related behavior and well-being (Lowry et al, 2020 ; McQuillan et al, 2022 ). Thus, for studies primarily seeking to understand the lived experience and consequences of infertility, it is reasonable to focus on questions about perceptions even if we are not certain that all respondents will interpret them in the same way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless—as noted above—there are good reasons to study self-perceived infertility. Self-perception measures are often the only measures available to us in surveys, and self-perceived infertility has been associated with both infertility-related behavior and well-being (Lowry et al, 2020 ; McQuillan et al, 2022 ). Thus, for studies primarily seeking to understand the lived experience and consequences of infertility, it is reasonable to focus on questions about perceptions even if we are not certain that all respondents will interpret them in the same way.…”
Section: Discussionmentioning
confidence: 99%
“…Lowry et al ( 2020 ) showed that self-perceived infertility explains more of the variance in depressive symptoms than medically defined infertility. Thus, for studies primarily seeking to understand the lived experience and consequences of infertility, it is generally reasonable to rely upon survey questions that indicate whether people perceive themselves to be infertile (Lowry et al, 2020 ; McQuillan et al, 2022 ).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Moreover, respondents who were pregnant or whose partners were pregnant were not asked the perceived fecundity questions, as pregnancy signifies fertility. Their OPF and PPF were treated as definitely yes following McQuillan et al (2022). Similarly, individuals or partners who were sterilized were categorized as definitely no for their respective OPF or PPF.…”
Section: Methodsmentioning
confidence: 99%
“…Most psychosocial research on this issue is cross-sectional, and has focused on clinical samples. The contribution by McQuillan et al (2022, this issue) provides strong evidence of a negative association between the perceived inability to procreate and life satisfaction using German panel data by applying fixed-effects modeling techniques, and thus implicitly controlling for all potential time-constant predictors of an individual’s well-being.…”
Section: Overview Of Papers In This Special Collectionmentioning
confidence: 99%